Scholar Opinion on Providing for Wives Who Do Not Live in The Same House (Qawanin Jurnal Ilmu Hukum, 2024)
When a man and a woman are married, they officially have responsibilities towards each other. And one of the responsibilities of a husband after marriage is to provide his wife with a place to live and provide for him. The income in question is either a physical income or an inner bread. If a husband deliberately fails to provide for his wife, then the husband is considered negligent and sinful. Because it is one of his responsibilities. Livelihood is not only a gift given by a husband to his wife, but also an obligation between the father and his children and also has a responsibility between an owner and something he owns. This income also covers the needs of the wife during childbirth, such as the financing of midwives or doctors who help with childbirth, drug costs and hospitals. Also included is the fulfillment of the biological needs of the wife. This income also covers the needs of the wife during childbirth, such as the financing of midwives or doctors who help with childbirth, drug costs and hospitals. Also included is the fulfillment of the biological needs of the wife.